The effect of artistic gymnastics talent scouting application to artistic gymnastic basic skills - Sukamti, E. R.; Pranatahadi, S. (Advances in Social Science, Education and Humanities Research, 2018)
The development of gymnastics athlete performance in Indonesia did not show significant progress over the years. Talent scouting is the important basic in achieving optimal performance. The aim of this study is to determine the effect of Artistic Gymnastics Talent Scouting Application to Artistic Gymnastic Basic Skills. A descriptive qualitative method study was developed using a survey technique. The sample was defined as 100 students, with 7-9 years old from Sleman area. Tests and measurements of anthropometry, biomotor, and gymnastic basic skills were used as data collection techniques. The early age artistic gymnastic talent scouting software was used as data analysis techniques with the aim to determine the category of talented sample research. The results showed that there are 3 talented students, 46 students are quite talented, 50 less talented students, and 1 student is not talented. The results showed that there is no significant effect of Artistic Gymnastics Talent Scouting Application to Artistic Gymnastic Basic Skills (p=, 214)